Effects of Seawater on Setting Time and Compressive Strength of Concretes with Different Richness - Ghazal, Ahmed I.; El-Sheikh, Mohammed Y.; Abd El-Rahim, Ahmed H. (Salehan Institute of Higher Education, 2021)
Water is one of the main constituents of concrete. Although many types of water exist, fresh water is the mostly used in concrete industry. Fresh water is expected to be in a great shortage by 2050 according to UN world water development report. Incorporating seawater in concrete mixture can help in the expected problem of scarcity of fresh water. Also, in many cases seawater may be the only available water especially in coastal regions. Many reports mention various possibilities of using seawater in concrete without detrimental effect on concrete properties. In this study another beneficial effect of seawater over tap water was concluded. Setting tests of cement paste mixed with seawater was determined using Vicat apparatus and compared to tap water. Compressive strength tests at the age of 28 days of Portland cement concretes with varied quantity of cement i.e. 300, 350, 400, 450, and 500 kg, and mixed with seawater was also performed and compared to tap water. The results show that seawater affects standard consistency of cement paste and two percent increase was required in order to attain the same consistency as tap water. It shows also seawater slightly accelerates initial setting of cement but the effect is not so pronounced so as to cause a trouble in concrete and final setting time almost remains unaltered. Compressive strength tests show an increase in concrete strength mixed with seawater for all tested mixtures and depending on quantity of cement. It also shows a beneficial effect of seawater on compressive strength of rich concrete with quantity of cement 450 and 500 kg over tap water.Â Doi: 10.28991/cej-2021-03091695 Full Text: PDF